2003
DOI: 10.1637/7007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chicken Anemia Virus DNA in Embryonal Tissues and Eggshell Membranes

Abstract: Chicken infectious anemia virus (CIAV) is a ubiquitous and highly resistant virus of chickens that causes anemia and death in chicks less than 3 wk of age and immunosuppression in chickens older than 3 wk of age. The production of specific-pathogen-free eggs free of CIAV is essential for research and vaccine production. Currently, flocks are screened for CIAV by antibody tests to ensure freedom from CIAV infection. Recent evidence, however, indicates that chickens may carry and vertically transmit CIAV DNA ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
1
26
0
1
Order By: Relevance
“…A alta sensibilidade da "nested-PCR" também é uma característica importante nas investigações que visam determinar a transmissão vertical do vírus ou a provável latência do mesmo (Todd et al 1992, Miller et al 2003. Ao realizar a "nested-PCR" com soro de matrizes com anticorpos para CAV, constatou-se que o DNA do agente pode persistir mesmo depois de ocorrida a soroconversão, como igualmente observado por outros autores (Cardona et al 2000).…”
Section: Discussão E Conclusões Discussão E Conclusões Discussão E Counclassified
“…A alta sensibilidade da "nested-PCR" também é uma característica importante nas investigações que visam determinar a transmissão vertical do vírus ou a provável latência do mesmo (Todd et al 1992, Miller et al 2003. Ao realizar a "nested-PCR" com soro de matrizes com anticorpos para CAV, constatou-se que o DNA do agente pode persistir mesmo depois de ocorrida a soroconversão, como igualmente observado por outros autores (Cardona et al 2000).…”
Section: Discussão E Conclusões Discussão E Conclusões Discussão E Counclassified
“…CAV infects T cell precursors in the thymic cortex and CD8 + splenic lymphocytes and haemocytoblasts in the bone marrow (Adair, 2000;Jeurissen et al, 1992;Noteborn et al, 1994a). There is also evidence that CAV can be present in the reproductive system (Cardona et al, 2000a, b) and be vertically transmitted in antibody-positive or -negative hens (Miller et al, 2003).Sequences in the 59 non-transcribed region of the CAV genome are believed to be the sole promoter enhancer for CAV (Noteborn et al, 1994b;Phenix et al, 1994). This region has four or five direct repeat (DR) regions of 21 bases, with a 12 base insert between the first two (or three) and the last two DR.…”
mentioning
confidence: 99%
“…The most wellcharacterized is chicken ovalbumin upstream promoter transcription factor 1 (COUP-TF1) (Cooney et al, 1993;Park et al, 2003). Together, these nuclear receptors can bind a wide range of ERE-like motifs and often compete for binding to the same DNA sequence.Due to the common occurrence of seroconversion at the time of sexual maturation in specific-pathogen-free flocks (Miller et al, 2001) and the presence of viral DNA in male and female gonads (Cardona et al, 2000b) and in freshly laid fertilized eggs (Miller et al, 2003), we hypothesized that CAV gene regulation is influenced by the regulation of Miller et al, 2005), and that the ERE-like sequences from the CAV promoter could compete for binding to unidentified proteins recognizing a consensus ERE. This suggested that members of the nuclear receptor superfamily provide a mechanism to regulate CAV activity when low viral genome copy numbers are present (Miller et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations